AN IMPLEMENTATION OF PARTICIPATIVE IQRO METHOD IN THE ORIENTED OF AL-QURAN EDUCATION CENTER ON THE PURPOSE OF LEARNING GOAL AND OBJECTIVES FOR EARLY CHILDREN - Chandra Asri Windarsih (IKIP Siliwangi Bandung, 2019)
Learning to read and write the Quran using the IQRO method has been used for a long time and applied to children. The basic reason is that with IQRO it is very easy for children to follow, the book is cheap consisting of six books that have a certain level. This research wants to collaborate with the learning goal method and objectives oriented. Hopefully, that early childhood is easy to understand and easy to remember letters, to be able to read the Quran correctly. Formulation of the problem